The Integration of Islamic Finance in the Global Economy: Opportunities, Challenges, and Future Directions - Febrian Permana; Randa Fajar Saputra; Yusra Yusra; Nanda Suryadi; Zulfadli Hamzah (Yayasan Pendidikan Islam Al-Matani, 2024)
Islamic finance has experienced significant growth over the past few decades, differing significantly from the conventional financial system by adhering to key principles such as the prohibition of interest (riba) and speculation (gharar). This unique approach not only caters to followers of Islam but also attracts a global audience seeking ethical financial solutions. As Islamic finance reaches beyond Muslim-majority countries, its contribution to sustainable development and financial inclusion becomes substantial. However, this expansion also presents challenges, including the need for greater standardization and regulation to better integrate with the global economic system. Notable research from institutions such as the World Bank and the International Monetary Fund emphasizes the sector's potential to address broader economic issues such as poverty and inequality. This thesis explores the integration of Islamic finance into the global economy, examining the factors driving its growth, the barriers faced, and its impact on economic development.